Signs and symptoms of developmental abnormalities of the genitourinary tract - Paulo Cesar Koch Nogueira; Isabel de Pádua Paz (Brazilian Society of Pediatrics, 2016)
Objective: The abnormalities of the genitourinary tract development are the leading cause of chronic kidney disease (CKD) in children. The diagnosis of this disease in Brazil is late and incomplete, which results in increased morbidity and mortality in this age group. Early diagnosis of this condition is the prerogative of generalist pediatricians, and the aim of this study was to review the clinical signs and symptoms associated with developmental abnormalities of the genitourinary tract. Data sources: Based on the description of a symbolic clinical case, the authors conducted a non‐systematic review of medical literature. Data synthesis: The results suggest that the following data should be used as a warning for early diagnosis of affected children: a) combined urinary tract abnormalities (chromosomal abnormalities; sequence of malformations [VACTERLand Prune‐Belly]; and musculoskeletal, digestive tract, heart, and nervous system malformations); b) previous history (congenital anomalies of the kidney and urinary tract [CAKUT] in the family, low birth weight, and oligoamnios); c) clinical signs (polyuria/nocturia, urinary tract infection, systemic arterial hypertension, failure to thrive, weak urinary stream, difficulty to start urination, distended bladder, non‐monosymptomatic enuresis, urinary/urge incontinence, and bowel and bladder dysfunction); and d) pre‐ and postnatal ultrasonographic alterations (increased anteroposterior diameter of the renal pelvis, mainly in the third trimester of pregnancy; single kidney; hydronephrosis associated with other abnormalities; and hydronephrosis with parenchymal involvement in the post‐neonatal assessment). Conclusion: The suggestions shown here can help the pediatrician to establish clinical hypotheses for the early diagnosis of developmental abnormalities of the genitourinary tract without resorting to expensive and invasive procedures.